Pengaruh Fasilitas Kamar terhadap Kepuasan Tamu di Hotel Hyatt Regency Yogyakarta - Wahyuni, Cica; Yuliana, Yuliana; Pramudia, Heru (Journal of Home Economics and Tourism, 2016)
This research is a form of associative research with survey method. The goal is to see how big the effect of variable-room amenities is to the guest satisfaction at the Hyatt Regency Yogyakarta. In this study the amount of guest who stayed was 8837 people (per month). And 99 people were taken as sample by using incidental sampling technique of sampling. Data collected by the indirect communication through a questionnaire, using â€œLikertâ€ scale, has been tested for validity and reliability. Engineering analysis is performed using computer program â€œSPSS version 16.0.Based on research the following results were obtained:(1) The room facility located in the pretty category (48.48%),(2) Satisfaction of the guests were in good category (43.43%),(3) The results of the simple linear regression hypothesis test obtained F count with sig. 0.000 <0.05, so variable room facility has a significant influence on guest satisfaction.Further R Square of 0.156. That means that room facilities affects the guest satisfaction.The remaining 15.6% is influenced by other factors such as customer service, check-in process, the overall food and beverages, sincerity of the staff, and condition of the hotel. Last is the regression coefficient. If Y = a + bX = 31 409 + 0.442 X means that every increase of 1 unit room facilities will increase 0, 442 units of guest satisfaction..Keywords: room facilities, guest satisfaction.